The Efficacy of IPL in Periorbital Skin Rejuvenation: An Open-Label Study - Barikbin, Behrooz; Akbari, Zahra; Vafaee, Reza; Razzaghi, Zahra (Journal of Lasers in Medical Sciences, 2019)
Introduction: Intense Pulsed Light (IPL) is one of the effective methods used to treat the signs of facial aging. However, its efficacy in improving the appearance of periorbital wrinkles has always been evaluated in the context of whole-face rejuvenation and not studied in its own right. Therefore, in this study we sought to examine the effectiveness and side effects of IPL in periorbital skin rejuvenation. Methods: In this uncontrolled, open-label clinical trial, 38 patients referred to the Behrooz professional skin clinic for signs of periorbital skin aging were recruited. Patients underwent three treatment sessions with IPL, at one-month intervals, and were evaluated for treatment side effects after each session. Six months after the final IPL session, patients were examined to assess the level of symptom improvement. Patients were photographed at each treatment session and at the six-month follow-up visit. Before and after patient images were evaluated by two dermatologists unaffiliated with the study to determine the extent of improvement in the appearance of wrinkles and skin texture. Results: Six months post-treatment, excellent improvement was observed in 3 patients (9.1%), considerable improvement in 7 patients (21.2%), moderate improvement in 9 patients (27.3%), mild improvement in 9 patients (27.3%) and finally little or no improvement was observed in 5 patients (15.1%). Comparison of improvement scores based on Fitzpatrick skin phenotype did not show significant differences (p=0.674). 4 patients (12.1%) were dissatisfied with the treatment whilst 17 patients (51.5%) reported moderate to considerable satisfaction with IPL rejuvenation. Conclusion: During whole face rejuvenation, IPL can be used to improve periorbital skin aging.